2021
DOI: 10.3390/app11209533
|View full text |Cite
|
Sign up to set email alerts
|

A Laser Irradiation Method for Controlling Pieris rapae Larvae

Abstract: At present, chemical pesticides remain the main approach for controlling Pieris rapae (L.) (Lepidoptera: Pieridae). This research proposes a novel laser irradiation method for managing P. rapae larvae as an alternative to chemical control. The effectiveness of controlling larvae and the influencing factors of lasers were studied to estimate optimal parameter combinations. Tests using the antifeedant effect and mortality of the larvae as dependent variables showed that the laser power, irradiation area, laser o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This has been proven by several studies. The P. rapae antifeedant larvae are cruciferous pests (which have an impact on cruciferous plants as they consume all of their leaves and can even cause soft rot) were the subject of another study conducted by Li et al (2021). The authors found that within 24 h there was a 100% mortality rate.…”
Section: Effect Of Laser Light On Organisms: Insectsmentioning
confidence: 99%
“…This has been proven by several studies. The P. rapae antifeedant larvae are cruciferous pests (which have an impact on cruciferous plants as they consume all of their leaves and can even cause soft rot) were the subject of another study conducted by Li et al (2021). The authors found that within 24 h there was a 100% mortality rate.…”
Section: Effect Of Laser Light On Organisms: Insectsmentioning
confidence: 99%
“…The hyperspectral data of the 7th to 9th abdominal segments of Pieris rapae were used as the hyperspectral data of this Pieris rapae [29]. In each group, the mean reflectance at the 7th to 9th abdominal segments of 5 Pieris rapae was taken as the spectral reflectance of this group [30]. The 5-point weighted smoothing of spectral data obtained by MATLAB software can effectively eliminate the influence of interference factors of original spectral data [31].…”
Section: Hyperspectral Testmentioning
confidence: 99%